2019
DOI: 10.1159/000498966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Accuracy of the Endoscopic ABC Classification System in Diagnosing Helicobacter pylori-Infected Gastritis

Abstract: Aims: Evaluating the accuracy of the modified Endoscopic ABC (Endo ABC) classification with an electronic endoscopy with narrow band imaging without magnification in diagnosing Helicobacter pylori (H. pylori)-infected gastritis. Methods: A total of 576 patients were enrolled and they underwent modified Endo ABC. They were stratified into 5 groups (A to E) based on the grades of endoscopic findings. H. pylori-infected gastritis status was determined in the following ways: current H. pylori gastritis was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Two studies used retrospective image collection but were deemed only medium risk of bias; these were therefore included in the analysis. 37,38 Overall, the studies showed low risk of bias and good applicability. The results are displayed in Figure 2.…”
Section: Quality Assessmentmentioning
confidence: 85%
See 1 more Smart Citation
“…Two studies used retrospective image collection but were deemed only medium risk of bias; these were therefore included in the analysis. 37,38 Overall, the studies showed low risk of bias and good applicability. The results are displayed in Figure 2.…”
Section: Quality Assessmentmentioning
confidence: 85%
“…47 This has encouraged the development of classification systems such as the Endoscopic ABC 48 which show a high degree of accuracy for prediction of H pylori status. 37 The interpretation of endoscopic findings remains complex however, and a simple identification system for the general endoscopist would be of use to allow rapid diagnosis of H pylori status in a less specialist setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, we selected the gastric site for assessment of the GC risk based on the assumption that premalignant changes in the stomach could spread from one part to another. To differentiate the moderate‐ and low‐risk groups, we restricted the images to the antrum and lesser curvature of the gastric body because the initial change of H. pylori infection appears in these regions of the gastric body . To differentiate the moderate‐ and high‐risk groups, we restricted the images to the gastric body and fornix because morphological changes in these regions may be more closely related to the risk of GC than those in the antrum .…”
Section: Discussionmentioning
confidence: 99%
“…Previous H pylori‐ induced gastritis could be detected using Endo E with an accuracy of 97% and a PPV of 100%, and using Endo D with an accuracy of 87%. The data presented defined new endoscopic tools as potential alternatives for detection of H pylori‐ induced gastritis without further diagnostic measures …”
Section: Gastric Diseasesmentioning
confidence: 99%